Prévenir et agir sur les violences à caractère sexuel : lorsque la qualité des soins de santé dédiés aux personnes concernées se heurte au déficit de crédibilité - Sandrine Vallée-Ouimet; Lisandre Labrecque-Lebeau; Pierre Pariseau-Legault; Audrey Bujold
Quebec is moving towards the recognition of sexual violence (SV) as a public health issue considering the seriousness of its consequences on victims' health. This recognition is taking place in the context of waves of denunciation (e.g. #Metoo of 2017). The failure to make the phenomenon intelligible has the effect of unfairly affecting the credibility of SV victims, who are often not taken seriously by public institutions. Several authors have studied the impact of this credibility deficit in judicial contexts, but few have focused on the institutional process inherent in healthcare facility. Based on a systematic review of the literature on care practices for victims of SV, this article has two objectives. Firstly, we wish to contribute to the collective reflection on the prevention and care of SV victims, in order to better understand the epistemic injustices (EI) they experience. Secondly, we would like to suggest avenues of reflection for caregivers, to raise their awareness of EIs and promote support for victims and prevention of SV.